Freedom and experimentation: ideas around the work of Teixeira Coelho (Revista NUPEART, 2025)
This article seeks to reflect on aspects of Teixeira Coelho's performance and production. A pioneer in understanding culture as a field of knowledge, the Professor Emeritus of the School of Communications and Arts at the University of São Paulo contributed to expanding the presence of the idea of ​​culture in the scope of human sciences inside and outside Brazil. Teixeira Coelho is a creator of ideas and cultural actors, with freedom as his guiding element. Faithful to art, he did not give up on it in the construction of his legacy, understanding it as an exacerbation and exasperation of culture.
Keywords: Teixeira Coelho; culture; art; freedom